2006
DOI: 10.1007/s11892-006-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

The renin-angiotensin system and its blockade in diabetic renal and cardiovascular disease

Abstract: Diabetic nephropathy, the most common cause of end-stage renal disease in the United States, is also associated with increased cardiovascular mortality. The renin-angiotensin-aldosterone system (RAAS) plays a central role in the development and progression of kidney disease and cardiovascular disease. Randomized, controlled trials have demonstrated renoprotection with the use of angiotensin receptor blockers (ARBs) in type 2 and angiotensin-converting enzyme inhibitors (ACEIs) in type 1 diabetes. More recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
(47 reference statements)
0
8
0
1
Order By: Relevance
“…Conversely, Christiansen et al showed that increased heart rate and cardiac contractility preexisted microalbuminuria, suggesting that the above factors may contribute to renal hyperperfusion and glomerular hyperfiltration, findings which are observed in T1DM patients, before the development of microalbuminuria [49]. Recently, it was suggested that the renin-angiotensin-aldosterone system might play a central role in the development and the progression of renal as well as cardiovascular impairment in patients with T1DM, while randomized, controlled trials demonstrated beneficial effects on renal and cardiovascular function of the use of angiotensin-converting enzyme inhibitors [50].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Christiansen et al showed that increased heart rate and cardiac contractility preexisted microalbuminuria, suggesting that the above factors may contribute to renal hyperperfusion and glomerular hyperfiltration, findings which are observed in T1DM patients, before the development of microalbuminuria [49]. Recently, it was suggested that the renin-angiotensin-aldosterone system might play a central role in the development and the progression of renal as well as cardiovascular impairment in patients with T1DM, while randomized, controlled trials demonstrated beneficial effects on renal and cardiovascular function of the use of angiotensin-converting enzyme inhibitors [50].…”
Section: Discussionmentioning
confidence: 99%
“…Type I diabetes has been associated with natriuresis and diuresis, as well as activation of vasopressin and the reninangiotensin-aldosterone system (7,84). Several groups have examined the regulation of sodium transporters in type I diabetic rodents (47,57,91,92,97,109,124).…”
Section: Altered Expression Of Sodium Transporter and Channels In Diamentioning
confidence: 99%
“…Despite the renoprotective effects reported in recent years, antihypertensive agents such as angiotensinconverting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) cannot completely prevent the progression of diabetic nephropathy and merely delay the onset of ESRD (Kalantarinia and Okusa, 2006). Therefore, a new drug for treatment of diabetic nephropathy based on a different mechanism of action is awaited with anticipation.…”
mentioning
confidence: 99%